Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11764-015-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and social support for healthy eating among Latina breast cancer survivors: implications for social and behavioral interventions

Abstract: Purpose Little is known about Latina breast cancer survivors' social networks or their perceived social support to achieve and maintain a healthy diet. This paper describes the social networks and perceived support for healthy eating in a sample of breast cancer survivors of predominantly Dominican descent living in New York City. Methods Spanish-speaking Latina breast cancer survivors enrolled in a randomized controlled trial of a culturally-tailored dietary intervention. Social networks were assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 35 publications
5
40
0
Order By: Relevance
“…The increase in number of cases from year to year is due to the increase in the awareness of women's on the disease, its prognosis and early screening and diagnosis (6, 7) More than 50% of breast cancer occurs in premenopausal women, aged younger than 40 years and/or with stage 3 disease (7) or age of the women ranged from 20 to 88 years (median age 43.0 years) (6) due to women's poor health seeking behaviors on quality of medical and nursing care, having children in their young age, low socio-economic status of females to cover needs and expenses associated with cancer and poor awareness breast cancer symptoms, prevention mechanisms, risk factors, and treatment options. Deaths of females from breast cancer during their most productive years could result in tragedy for families, food insecurity and children's withdrawal from school, an increased work burden on children and loss of assets (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in number of cases from year to year is due to the increase in the awareness of women's on the disease, its prognosis and early screening and diagnosis (6, 7) More than 50% of breast cancer occurs in premenopausal women, aged younger than 40 years and/or with stage 3 disease (7) or age of the women ranged from 20 to 88 years (median age 43.0 years) (6) due to women's poor health seeking behaviors on quality of medical and nursing care, having children in their young age, low socio-economic status of females to cover needs and expenses associated with cancer and poor awareness breast cancer symptoms, prevention mechanisms, risk factors, and treatment options. Deaths of females from breast cancer during their most productive years could result in tragedy for families, food insecurity and children's withdrawal from school, an increased work burden on children and loss of assets (8).…”
Section: Introductionmentioning
confidence: 99%
“…One study has discovered that females with few social connections had a 43 percent higher risk of breast cancer returning, compared to well-connected females.. Likewise, the isolated female was 64 percent more likely to die from breast cancer and 69 percent more possible to die of any cause during the the study, compared to their complements with many social bonds (8).…”
Section: Introductionmentioning
confidence: 99%
“…While cooking-related behaviors and psychosocial determinants related to barriers to cooking have been well described (Adams et al, 2015; Crookes et al, 2016; Garcia, Reardon, McDonald, & Vargas-Garcia, 2016; Mills et al, 2017), psychosocial outcomes from cooking interventions have not. We hypothesize that there may be psychosocial benefits to participating in cooking interventions that potentially have clinical and public health implications.…”
mentioning
confidence: 99%
“…Reports indicated that breast cancer was the common cancer which accounts around 33% of all female cancer cases (4). Food insecurity and children withdrawal from school, increased work burden on children and loss of assets were the common problems following death of women with breast cancer during their most productive years (5).…”
Section: Introductionmentioning
confidence: 99%